New limit on Lorentz-invariance- and CPT-violating neutron spin interactions using a free-spin-precession 3He-129Xe Comagnetometer - Allmendinger, Fabian; Heil, W.; Karpuk, S.; Kilian, W.; Scharth, A.; Schmidt, Ulrich; Schnabel, A.; Sobolev, Yu.; Tullney, K. (Physical review letters, 2014)
We report on the search for a CPT- and Lorentz-invariance-violating coupling of the 3He and 129Xe nuclear spins (each largely determined by a valence neutron) to posited background tensor fields that permeate the Universe. Our experimental approach is to measure the free precession of nuclear spin polarized 3He and 129Xe atoms in a homogeneous magnetic guiding field of about 400 nT using LTC SQUIDs as low-noise magnetic flux detectors. As the laboratory reference frame rotates with respect to distant stars, we look for a sidereal modulation of the Larmor frequencies of the colocated spin samples. As a result we obtain an upper limit on the equatorial component of the background field interacting with the spin of the bound neutron ˜bn⊥<8.4×10−34 GeV (68% C.L.). Our result improves our previous limit (data measured in 2009) by a factor of 30 and the world’s best limit by a factor of 4.
Im Titel sind die Zahlen 3 und 129 hochgestellt
Gesehen am 09.09.2020